Isolement et identification des bactéries lactiques à partir des fruits et légumes frais - Demir, Ibtissem; Belarbi, Sara (My University, 2020)
Recently, great interest is consecrated to lactic acid bacteria who have great beneficial properties for human health. This work is carried out to assess scientific studies about lactic acid bacteria (LAB) isolated from somelocal fresh fruits and vegetables. Five samples of fruit and vegetable (Strawberry, orange, tomato and cabbage) were chosen to isolate lactic strains.Preliminary phenotypic characterization tests (Growth temperature, Gram stain, catalase test) were studied. Then, the various biochemical tests that should be carried out for the purification and identification of the isolates were detailed. Finaly, some scientific articls were selected to be analysed in order to demonstrate the value of using indigenous lactic acid bacteria of fruits and vegetables.
Keywords: Lactic acid bacteria; fruits; vegetables; isolation; phenotypic characterization.